O Rio Amazonas no percurso poético de Thiago de Mello e de Juan Carlos Galeano - Barbosa Neto, Antonio Felipe (2019)
Contemporary Latin American literature, specifically the Amazonian, has presented a perspective instigated by the factual aspects of man and nature in degradation. The effects of the slow violence on the forest spaces and the people that inhabit them, has awakened the ethical and political, nonpartisan position of the local writers, who come out in defence of the historically marginalized subjects, placing themselves as voices that reverberate the changes of the Amazon landscape.With regard to the image of nature, the present work, together with the appreciation of the native culture, is analyzed in the texts, noticing how the literary construction of the Amazon has helped in the process of raising awareness about environmental and social problems in the region. For this, we searched through the representations of the river element, found in the ecopoetic of the brazilian writer Amadeu Thiago de Mello, in the work Amazônia pátria da água (1987), as well as in the book Amazonia y otros poemas (2004), by the colombian poet Juan Carlos Galeano, to observe how the authors attribute the subjectivity to the amazonian waters. The river, therefore, enters our study as a symbolic aesthetic resource responsible for conditioning the imaginative path of poetry, permeated by the popular character that reinforces the position of belonging to discourses. It is noteworthy that the Amazon and other tributaries are also characterized as responsible for denunciations, subjective beings that outsource the effects of environmental degradation. The poetry and poems to be studied are analyzed by means of the spatial representation of the poetry, in which we seek to trace an analysis of the poetic narrative by means of an ecocritical reading method based on the following aspects: analysis of the texts in their representations of the environment as a political and aesthetic issue; identification of the ecological problems that are covered by the elements related to ecopoietic discussion; and finally, to relate poetic voices as a form of specific environmentalism. In this way, we propose to dialogue with the works, seeking to identify the waters as an environment subjectivized by memories, marked by the presence of human and nonhuman creatures, and real and supernatural beings that permeate their existence. As main theoretical contributions, we seek to support in such names as: Coelho (1945); Mendes (1974); Leonel (1998); Mires (1990); Junk and Melo (1990); Allier (1992); Table (1993); Bhabha (1996); Morin (2001); Leff (2003); Mendes (2005); Nielson (2014); Oyarzún (2015); Coutinho (2003); Said (2007); Schneider (2007); Spivak (2010); Nixon (2011); Levy (2011); Walter (2012); Thiel (2012); Braga (2015). We have verified that the analyzed poetics reflect unique perceptions that are related in favor of a common struggle. The subjectivism attributed to the river reverberates in consonance with the universal symbology, however, imbued with a native perception that enables the reader an experience of empathy, of the recognition of life in its plurality.